Implementasi Pembelajaran Tatap Muka (PTM) Terbatas Selama Masa Pandemi Covid-19 di SMA N 1 Kubu - Piki Setri Pernantah; Rizatunnita Rizatunnita; Liza Kusnilawati; Ciptro Handrianto (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This article aims to discuss the process of implementation of Limited Face-to-Face Learning (PTM) during the Covid-19 Pandemic and the obstacles faced and efforts made in the smooth implementation of limited face-to-face learning at SMA N 1 Kubu, Riau, Indonesia. The research method used is a descriptive-qualitative method with data collection techniques through observation and interview activities that do not provide treatment, manipulation or changes in the variables studied. The results of this study showed that the application of limited face-to-face learning still follows the standards of health protocols, during learning has carried out 3M, namely wearing a mask before entering the classroom, washing hands using soap and running water and entering the classroom regularly and maintaining distance. Also implement learning strategies that include practice, discussion, reflection and feedback so as to make learning work effectively.